Problematika Kesiapan Pernikahan Individu Dewasa Awal - Shaqilla Aulia Hakim; Ulfa Masfufah (Flourishing Journal, 2023)
This article discusses the readiness of individuals in early adulthood to enter marriage. Marriage is a relationship forged by a man and a woman to balance life biologically, psychologically, and socially. Although an age above 19 years is considered ideal for marriage, the main factor in marriage is the agreement and readiness between both partners before marriage. The method used in this article is a literature review by analyzing the psychological impact of the lack of readiness for marriage in early adulthood. The results of this article show that marriage must be prepared physically, mentally, and financially, and factors such as self-disclosure, trust, equality, intimacy, good conflict management, and open communication also contribute to marital satisfaction. Emotional readiness and emotional intelligence are important in maintaining the continuity of marriage and household success. Marriage without careful consideration has the risk of causing depression in partners, especially women. Therefore, individuals must carefully consider wedding preparations to avoid long-term negative impacts and ensure the family remains harmonious. AbstrakArtikel ini membahas tentang kesiapan individu pada masa dewasa awal dalam memasuki pernikahan, sebagai salah satu tugas perkembangan pada masa ini. Meskipun usia di atas 19 tahun dianggap ideal untuk menikah, faktor utama dalam pernikahan adalah persetujuan dan kesiapan yang disepakati oleh kedua pasangan sebelum melangsungkan pernikahan. Metode yang digunakan dalam artikel ini adalah review literatur dengan menganalisis dampak psikologis yang muncul akibat kurangnya kesiapan dalam pernikahan pada masa dewasa awal. Hasil dari artikel ini dapat diketahui bahwa pernikahan harus dipersiapkan secara fisik, mental, dan finansial, serta faktor-faktor seperti self-disclosure, kepercayaan, kesetaraan, keintiman, pengelolaan konflik yang baik, dan komunikasi yang terbuka juga berkontribusi pada kepuasan pernikahan. Kesiapan emosional dan kecerdasan emosi memainkan peran penting dalam menjaga kelangsungan pernikahan dan keberhasilan rumah tangga. Pernikahan tanpa pertimbangan yang matang berisiko menyebabkan depresi pada pasangan, terutama perempuan. Oleh karena itu, penting bagi individu untuk memikirkan persiapan pernikahan dengan matang agar terhindar dari dampak negatif jangka panjang.